2006
DOI: 10.4161/auto.2984
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and Lysosomes in Pompe Disease

Abstract: In Pompe disease, a deficiency of lysosomal acid alpha-glucosidase, intralysosomal glycogen accumulates in multiple tissues, with skeletal and cardiac muscle most severely affected.(1) Complete enzyme deficiency results in rapidly progressive infantile cardiomyopathy and skeletal muscle myopathy that is fatal within the first two years of life. Patients with partial enzyme deficiency suffer from skeletal muscle myopathy and experience shortened lifespan due to respiratory failure. The major advance has been th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 107 publications
(75 citation statements)
references
References 10 publications
4
69
1
1
Order By: Relevance
“…Furthermore, we have shown that autophagic accumulation in muscle fibers was associated with resistance to enzyme replacement therapy. [21][22][23] We now demonstrate that the underlying skeletal muscle pathology and the extent of autophagy in Pompe patients are similar to those in mice. Autophagy appears to play a major role in the pathogenesis of the disease, a finding that has important implications for the effectiveness of enzyme replacement therapy with the recombinant human acid a-glucosidase.…”
Section: Introductionsupporting
confidence: 53%
“…Furthermore, we have shown that autophagic accumulation in muscle fibers was associated with resistance to enzyme replacement therapy. [21][22][23] We now demonstrate that the underlying skeletal muscle pathology and the extent of autophagy in Pompe patients are similar to those in mice. Autophagy appears to play a major role in the pathogenesis of the disease, a finding that has important implications for the effectiveness of enzyme replacement therapy with the recombinant human acid a-glucosidase.…”
Section: Introductionsupporting
confidence: 53%
“…Glycogen is also transported to lysosomes where it is directly hydrolyzed to glucose by a lysosomal ␣-glucosidase (acid maltase) (6). Although probably not the major degradative mechanism under normal circumstances, the significance of this pathway is emphasized by the symptoms of patients with Pompe disease in which the ␣-glycosidase gene is mutated (7)(8)(9). The severity of the phenotype varies with the degree of impairment of glycosidase activity, in the worst cases leading to death within the 1st year after birth.…”
mentioning
confidence: 99%
“…This model of Pompe disease has massive overaccumulation of glycogen in the lysosomes of skeletal muscle as well as large accumulation of autophagic vesicles containing polysaccharide in some fiber types [34,35]. Our results could be rationalized if laforin did not have access to the bulk of the glycogen present in GAA −/− muscle.…”
Section: Resultsmentioning
confidence: 69%